Precipitation polymerization - Khan, Sabir [UNESP]; Vega-Chacón, Jaime; Ruiz-Córdova, Gerson A.; Pizan-Aquino, Charles; Jara-Cornejo, Eduardo EJ [UNESP]; Torres, Sergio Espinoza [UNESP]; Jacinto-Hernández, C. [UNESP]; López, Rosario; Sotomayor, Maria D.P.T.; Picasso, Gino; Villa, Javier E.L. [UNESP] (Elsevier, 2022)
Polymerization method has become the most extended procedure of chemical synthesis, characterization of nanoparticles with novel morphology and their wide applications in separation, drug delivery via intravenous and some biological system and nanotechnology. Polymerization by precipitation is based on the development of uniform and clean polymer particles, such as microspheres, nanoparticles, core–shell particles, and hollow nanostructures. Although precipitation technique has low production efficiency, the low concentrations of the monomers maintain the stability of the particles. In this chapter, a general introduction of precipitation polymerization and their synthesis mechanisms like controlled radical precipitation polymerization, thermal, photopolymerization, accumulation, nucleation as applications is presented. The development of complex nanostructures and their applications in separation and drug delivery is highlighted as well.
Keywords: application; Precipitation polymerization; self-stabilized precipitation polymerization; synthesis